THE IINFLUENCE OF ELECTRONIC WORD-OF-MOUTH, SERVICE QUALITY, DESTINATION IMAGE AND SATISFACTION TOWARD REVISIT INTENTION (STUDY ON BUKITTINGGI CITY, WEST SUMATERA) - Ahmad Istiqlal Ahlunnazak; Abror Abror (Jurnal Ecogen, 2019)
The purpose of this research are to analyze : (1) the effect of E-WOM on Destination Image of Bukittinggi City (2) the effect of E-WOM on Satisfaction of Bukittinggi City (3) the effect of Service Quality on Destination Image of Bukittinggi City (4) the effect of Service Quality on Satisfaction of Bukittinggi City (5) the effect of Destination Image on Revisit Intention of Bukittinggi City (6) the effect of Satisfaction on Revisit Intention of Bukittinggi city. The type of this research is causative research. The population of this research is the padang society who has visited Bukittinggi City. Total sample of this research was 208 people by using questionnaire. The results of this research show that (1) E-WOM has a significant & positive effect on Destination Image (2) E-WOM has a significant & positive effect on Satisfaction (3) Service Quality has a significant & positive effect on Destination Image (4) Service Quality has a significant & positive effect on Satisfaction (5) Destination Image has a significant & positive effect on Revisit Intention (6) Satisfaction has a significant & positive effect on Revisit Intention. Keyword: Electronic Word-Of-Mouth (e-WOM), Service Quality, Destination Image, Satisfaction,Revisit Intention